2019
DOI: 10.1088/1367-2630/ab0e1a
|View full text |Cite
|
Sign up to set email alerts
|

Remote control of cascading dynamics on complex multilayer networks

Abstract: To develop effective control strategies to enhance the robustness of multilayer networks against largescale failures is of significant value. We articulate the idea of 'remote control' whereby adaptive perturbations to one network layer are able to enhance the resilience of not only itself but also other interconnected network layers. We analyze the principle of remote control using percolation dynamics by showing analytically and numerically that, with the adaptive generation of a small number of new links in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…This is because the use of the deep learning model uses the historical structure of the network as the prior knowledge of the community detection at the current time, and the deep learning model obtains more input data when compared with the baselines. The research in community detection will further promote the development of the optimization of transportation network structures [30,31], the analysis of social networks [32,33], and research of biological systems [3,34].…”
Section: Resultsmentioning
confidence: 99%
“…This is because the use of the deep learning model uses the historical structure of the network as the prior knowledge of the community detection at the current time, and the deep learning model obtains more input data when compared with the baselines. The research in community detection will further promote the development of the optimization of transportation network structures [30,31], the analysis of social networks [32,33], and research of biological systems [3,34].…”
Section: Resultsmentioning
confidence: 99%
“…The study of detecting community structures in multilayer networks is experiencing a blossom in the last decade. Relevant researches cover various aspects among our daily life such as analyzing influential users in multiple social platforms (Al-Garadi et al 2018), finding organization of proteins in a biological system (Gosak et al 2018) and managing urban transportation system with various traffic manners (Liu et al 2019), etc. The following subsections summarized applications of community detection via a multilayer network framework.…”
Section: Applicationsmentioning
confidence: 99%
“…Compared with the minimum set of driver nodes identified in single-layer networks, more drug targets occurred in a multilayer network [ 11 , 12 , 13 ]. Liu et al [ 14 ] demonstrated that remote control can enhance the robustness of multilayer transportation systems against cascading failure. Simultaneously, the controllability of multilayer networks has become increasingly important, and researchers have paid much attention to it.…”
Section: Introductionmentioning
confidence: 99%